The pigeon finds a hot dog eaudiobook - Willems, Mo (Weston Woods, 2010)
When Pigeon finds a delicious hot dog, he can hardly wait to shove the entire thing in his beak. But . . . then a very sly and hungry duckling enters the scene and wants a bite. Who will be the more clever bird? In this hilarious follow-up to the acclaimed Don't Let the Pigeon Drive the Bus! Mo Willems has created another avian adventure that encourages children to share even their most prized processed foods. Mo Willems is a six-time Emmy Award-winning writer and animator for Sesame Street and the head writer of Cartoon Network's Code Name: Kids Next Door.